Backwardness advantage and economic growth in the information age: A cross-country empirical study - Khuong Vu; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This paper seeks to gain insights into whether developing countries benefit more from the backwardness advantage for economic growth in the Information Age. The paper examines this concern through three complementary approaches. First, it derives theoretical grounds from the existing economic models to support the hypothesis that the internet, inter alia, enables developing countries to reap greater growth gains from technology acquisition and catch-up. Second, the paper uses descriptive evidence to show that the growth landscape has indeed shifted decisively in favor of developing countries in the Internet Age in comparison to the preinternet period. Third, using rigorous econometric techniques with data of 163 countries over a 20-year period, 1996-2016, the paper evidences that developing countries on average reap significantly greater growth gains from internet adoption in comparison to the average advanced country. The paper discusses policy implications from the paper's findings.
Keywords: O40; 330; backwardness advantage; developing countries; internet; technology catch-up; GMM